Judges and Ethics: Understanding the Limits of Authority in Law Enforcement - Khadijah, Lussy Putri; Mariani, Mariani; Sukti, Surya (Ilmu Hukum Prima (IHP), 2025)
This study examines the ethical boundaries of judicial authority and their impact on law enforcement and public trust. The role of judges extends beyond merely applying legal principles; it also involves ethical considerations that ensure fairness, impartiality, and integrity in judicial decisions. This research employs a qualitative approach using a literature review method, analyzing legal documents, academic writings, and court rulings to explore the intersection of judicial ethics and the limits of authority. The findings reveal that ethical violations, such as conflicts of interest and abuse of power, significantly affect public perception of judicial credibility. Weak ethical supervision, personal interests, and ineffective accountability mechanisms contribute to these issues. To address these concerns, this study recommends stronger ethical training, enhanced oversight mechanisms, and institutional reforms to uphold judicial integrity. Implementing these measures is crucial for strengthening public confidence in the judiciary and ensuring the fair application of the law.